Safety, Efficacy and Indications of ?-Blockers to Reduce Heart Rate prior to Coronary CT Angiography-An Overview - Jahan, WA; Azam, A; Deena, S; Begum, W; Rahman, M (Cardiovascular Journal, 2012)
For selected indications, coronary computed tomographic (CT) angiography is an established clinical technology for evaluation in patients suspected of having or known to have coronary artery disease. In coronary CT angiography, image quality is highly dependent on heart rate, with heart rate reduction to less than 60 beats per minute being important for both image quality and radiation dose reduction, especially when single-source CT scanners are used. â-Blockers are the first-line option for short-term reduction of heart rate prior to coronary CT angiography. In recent years, multiple âblocker administration protocols with oral and/or intravenous application have been proposed.This review article provides an overview of the indications, efficacy, and safety of â-blockade protocols prior to coronary CT angiography with respect to different scanner techniques. Moreover,implications for radiation exposure and left ventricular function analysis are discussed DOI: http://dx.doi.org/10.3329/cardio.v5i1.12280 Cardiovasc. j. 2012; 5(1): 100-106